UNDERSTANDING THE CONCEPT OF SANKRAMIKA DADRU KUSTA- A CASE STUDY - Puripanda, *S Kamalakar; Raju B, Mahesh; KJ, Mallika; TB, Tripathy (International Journal of Ayurveda and Pharma Research, 2016)
Skin is a primary external covering of body mostly affected by fungal infections. In Ayurveda skin fungal infection is termed as Dadru (Tinea/Ringworm). It is one of the most common Twak Vikara affecting all the age group of population.. There is no separate mention of Nidana, Poorvarupa, Samprapti of Dadru, but the Samanya Nidana, Poorvarupa mentioned for Kusta can be considered here. Sankramika or Aupasargika Roga Nidanaof Kusta explained by Achaya Susrutha. Incidence rate of Dadru gradually increasing day to day because of improper Vihara like uncleanliness of body, sharing cloths of others etc., so this type of Dadru considered as Sankramika Vyadhi. These Sankramika Vyadhi spreads from person to person by Krimi through Sweda. Dadru can be diagnosed with the help of Varna (Raga), Samsthana (Pidika & Mandala), Adhistana (Twak). The knowledge of Nidana is helpful for the proper diagnosis, prevention of disease and treatment also. The physician who is having proper knowledge of Nidana means to cure the disease and their proper utilization. 'Nidana Parivarjana' is the main method of keeping oneself free from the disease. Krimi Gatha Dadru Vyadhi (Sankramika) has to be treated by Apakarshanam, Prakrithi Vigatha and Nidana Parivarjana. With the help of this principle the case of Sankramika Bahya Malaja Sitha type of Dadru Kusta successfully managed.